Ireland : Second Post-Program Monitoring Discussions; Staff Report; and Press Release. (IMF Staff Country Reports; Country Report, 2015)
Ireland's recovery has strengthened yet political challenges to adjustment appear to have increased. The recovery is led by job creation and investment financed by retained earnings rather than lending. But uncertainties around medium-term prospects are wide given external risks and domestic crisis legacies. Sustaining recovery and rebuilding space for policy maneuver are therefore key policy priorities. However, weak polls for the governing coalition and adjustment fatigue-reflected in widespread protests against water charges-may constrain policy efforts, as seen in limited fiscal adjustment in 2015. A clear strategy to underpin reaching budget balance in the medium term is needed:Budget balance is a sound medium-term goal as it will put Ireland's high public debt firmly on a downward path and enable fiscal policy to cushion the economy. As growth is likely to diminish over the medium term, steady structural adjustment of about 3/4 percent of GDP annually is appropriate to avoid undue drag on growth.A strategy is needed to achieve the restraint envisaged by the authorities in the face of strong spending pressures. Such a strategy should include reforms to generate savings while protecting core services, flexibility in reallocating spending, and preparedness to implement new measures including on the revenue side if needed.Completing bank repairs and ensuring financial resilience are needed to ensure a revival of bank lending that supports a lasting recovery: Although bank capitalization, liquidity, and profitability are much improved, nonperforming loans (NPLs) remain exceptionally high. Priorities are further progress on durable resolution of distressed mortgages-supported by more timely repossession proceedings to motivate borrower engagement on restructures-and ensuring steady workouts or disposals of distressed commercial loans.Recent proposals by the Central Bank of Ireland (CBI) to strengthen regulation of mortgage loan origination are a welcome step to increase the resilience of banks and households to property cycles and help moderate such cycles in future.